VISUAL DESIGN THINKING FOR DIGITAL BANKING: COMPARATIVE INSIGHTS FROM CO-OPERATIVE INSTITUTIONS - Bhosale, Jyotirmayee Vishvajit; Pisal, Deepali Satish (ShodhKosh: Journal of Visual and Performing Arts, 2025)
The high level of digitalization of financial services has altered customer-customer interaction with the banking platform, which has put visual design thinking at the center of innovation in digital banking. As commercial banks have actively pursued the user-centric digital interfaces, co-operative banking institutions that are based on shared values of communities and relationship-based services have distinct challenges and opportunities in how their ethos can become successful in digital experiences. This paper examines visual design thinking in digital banking and gives some comparative analysis on co-operative institutions and the mainstream commercial banks. The study analyzes the effect of the visual aspects of design like the simplicity of the interface, hierarchy of information, accessibility, the psychology of color and customer engagement to usability, trust, and customer engagement across digital banking systems. The research applies a comparative framework in the analysis of mobile and web interfaces of the chosen co-operative and commercial banks and is backed by the principles of user experience (UI) and design thinking phases such as empathize, define, ideate, prototype, and test. The specific focus is on the way co-operative banks are changing the visual design to suit different, often semi-urban and rural audiences with different degrees of digital literacy. The results have shown that commercial banks focus on efficiency and personalization and rich-features dashboards whereas co-operative institutions focus on clarity, familiarity and trust-building visuals. Nevertheless, inconsistencies, responsiveness, and compliance to accessibility still exist in most co-operative online platforms. The research paper has identified the best practices and design solutions that can help co-operative banks strike a balance between technological modernization and their social and community-based identity.